Controlling Intermediate Phase Formation to Enhance Photovoltaic Performance of Inverted FA-Based Perovskite Solar Cells - Li, Chaohui; Park, Hyoungwon; Qiu, Shudi; Streller, Fabian; Zhang, Kaicheng; Peng, Zijian; Byun, Jiwon; Tian, Jingjing; Maiti, Santanu; Xie, Zhiqiang; Dong, Lirong; Liu, Chao; et al. (ACS Energy Letters, 2024)
Formamidinium (FA)-based perovskites exhibit significant potential for highly efficient photovoltaics due to their promising optoelectronic properties and optimal bandgap. However, the undesired inactive phase arises from multiple crystal nucleation pathways formed by various intermediate phases during the film formation process, persistently accompanying it. FA-based perovskites frequently struggle to form uniform, highly crystalline films. This challenge complicates the development of reliable and highly reproducible crystallization processes for perovskites and the establishment of guidelines for controlling the α-phase formation. In this work, we investigate the role of poly(acrylonitril-co-methyl acrylate) (PAM) to simultaneously control nucleation and subsequent α-phase crystallization. This successfully demonstrates the regulation of oriented crystal growth through the creation of a PAM-PbI2 intermediate. Ultimately, PAM-modified p-i-n architecture devices obtain a promising power conversion efficiency (PCE) of 25.30%, with VOC (1.211 V), achieving 95% of the detailed balance limit. Additionally, PAM-modified devices maintain ≥90% of the initial efficiency for 1000 h under 1 sun and 65 °C operation.
CRIS-Team Scopus Importer:2024-11-22